2014
DOI: 10.1152/ajprenal.00679.2013
|View full text |Cite
|
Sign up to set email alerts
|

Role of spinal GABAAreceptors in pudendal inhibition of nociceptive and nonnociceptive bladder reflexes in cats

Abstract: Picrotoxin, an antagonist for γ-aminobutyric acid receptor subtype A (GABAA), was used to investigate the role of GABAA receptors in nociceptive and nonnociceptive reflex bladder activities and pudendal inhibition of these activities in cats under α-chloralose anesthesia. Acetic acid (AA; 0.25%) was used to irritate the bladder and induce nociceptive bladder overactivity, while saline was used to distend the bladder and induce nonnociceptive bladder activity. To modulate the bladder reflex, pudendal nerve stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 31 publications
4
48
0
Order By: Relevance
“…This is consistent with previous studies where administration of GABA A antagonists excited the bladder (24,27), although a recent study reported that picrotoxin increased bladder capacity in cats (56).…”
Section: Effectiveness Of Stimulation-evoked Inhibitionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with previous studies where administration of GABA A antagonists excited the bladder (24,27), although a recent study reported that picrotoxin increased bladder capacity in cats (56).…”
Section: Effectiveness Of Stimulation-evoked Inhibitionsupporting
confidence: 93%
“…Although previous reports suggested that separate pathways may govern inhibition of nociceptive and nonnociceptive bladder contractions (44,56), GABAergic mechanisms appear critical for inhibition of both types of contractions. A recent study of low-dose picrotoxin found that picrotoxin blocked inhibition of nociceptive, but not nonnociceptive, bladder contractions (56).…”
Section: Gabaergic Mechanisms Participate In Inhibition Of Both Nocicmentioning
confidence: 88%
See 1 more Smart Citation
“…Our previous studies in cat revealed that spinal GABA A receptors play an important role in pudendal neuromodulation of bladder overactivity (Xiao et al, 2014), whereas opioid and glycine receptors have no or a minor role (Mally et al, 2013;Rogers et al, 2016). In contrast, we showed that opioid receptors have an essential role in tibial neuromodulation of bladder overactivity in the cat .…”
Section: Introductionmentioning
confidence: 51%
“…On the other hand, inhibitory modulation of reflex bladder activity elicited by pudendal nerve stimulation (PNS) in the cat is markedly different than TNS and foot neuromodulation. PNS inhibition of bladder overactivity is resistant to naloxone (13), does not produce poststimulation inhibition (22), and is mediated in part by activation of GABAergic receptors in the spinal cord (31). PNS inhibition also has a different frequency-response curve, eliciting an increase in bladder capacity only at low frequencies (5-10 Hz) and not at higher frequencies (20 -40 Hz) (28).…”
Section: Discussionmentioning
confidence: 99%